ANALISIS SALURAN PEMASARAN DAN MARJIN PEMASARAN KELAPA DALAM DI DAERAH PERBATASAN KALIMANTAN TIMUR - Elly Jumiati, Dwidjono Hadi Darwanto, Slamet Hartono dan Masyhuri (Universitas 17 Agustus 1945 Samarinda, 2013)
This study aims to analyze the efficiency of marketing channels and marketing margins in the coconut. The method used is descriptive and analytical methods margin, distribution margins and share price received by farmers as well as the ratio of benefits and costs in the oil marketing. The results indicated that there were two oil marketing channels in the research sites, namely the channel I: farmer traders village/district – middlemen between districts/cities – consumer: and marketing channels II: farmer – traders village/district – traders collector between districts/cities – retailer – consumer where botk inefficient marketing channels and marketing of coconut in view of the value of margin, distribution margins and share price received by farmers, as well as the ratio of benefits and costs is also inefficient.